Territorial seismic risk assessment of a sample of 13 masonry churches in Tuscany (Italy) through simplified indexes. (15th May 2021) - Betti, Michele; Galano, Luciano; Lourenço, Paulo B.
Highlights: Sample of 13 Masonry Churches in Tuscany (Italy). Territorial Seismic Risk Assessment. Critical Insight into the Results obtained with expeditious approaches. Abstract: Among heritage buildings, masonry churches are complex structures often characterized by an open plan layout with slender perimeter walls. Their vulnerability to earthquakes is frequently increased by the absence of adequate connections between the various parts of the structural complex, together with the presence of thrusting horizontal elements such as masonry vaults and timber roofs. In this paper, the vulnerability and the seismic risk of thirteen masonry churches located in Tuscany (Italy) have been analysed with simplified methods to establish a first screening of the risk of this heritage typology. The methods are that proposed by Lourenço and Roque in 2006 and the so-called first level of analysis (LA-1), introduced by the Italian code. For one of these churches, the Basilica of San Francesco in Arezzo, the analyses of second (LA-2) and third (LA-3) level have been also performed according to the same code. The results highlight the contribution of the simplified approaches to establish a first selection of the priorities for subsequent investigations and, if needed, proper interventions. Approximately one-half of the churches composing the sample have the normalized simplified indexes lower than one, indicating the need of further investigations. For the Basilica of San Francesco the results of LA-2 level of analysis confirm the conclusions obtained with the more simplified procedures, while a criticism is highlighted with the LA-3 approach when the N2 method is adopted in combination with a pushover methodology of analysis.